Exploring Youth Worship Interest: The Impact of Full-band Music at HKBP Yogyakarta - Sitorus, Michael Putra Pratama; Samosir, Tanesya Hotris (Areopagus : Jurnal Pendidikan Dan Teologi Kristen, 2024)
This study investigates the impact of full-band music on the interest of youth in Sunday worship at HKBP Yogyakarta. Utilizing a quantitative research method, the independent variable is full-band music, while the dependent variable is the interest of young congregants. A sample of 67 individuals was drawn from a population of 670 using random sampling techniques. Data collection involved observations, interviews, questionnaires, and documentation. The questionnaire, based on indicators of interest and musical elements, was validated for reliability using a Likert scale. Results indicate a significant positive correlation between full-band music and youth interest, with a coefficient of determination (r²) of 0.26. This suggests that while full-band music positively influences youth engagement, 74% of their interest is affected by other factors. This research contributes to enhancing worship music services at HKBP Yogyakarta and offers insights for future studies on the role of worship music in engaging youth. The findings aim to serve as a reference for academics and practitioners seeking to improve the quality of worship music.